Virtual research visits and direct-to-consumer genetic testing in Parkinson's disease. (June 2015) - Dorsey, E Ray; Darwin, Kristin C; Mohammed, Samara; Donohue, Sean; Tethal, Alyssa; Achey, Meredith A; Ward, Susan; Caughey, Elaine; Conley, Emily D; Eriksson, Nicholas; Ravina, Bernard
Objective: The purpose of this study was to conduct a proof-of-concept study to evaluate remote recruitment and assessment of individuals ("virtual research visits") with Parkinson's disease who have pursued direct-to-consumer genetic testing. Methods: Participants in 23andMe's "Parkinson's Research Community" were contacted by 23andMe. Fifty willing participants living in 23 states underwent a remote, standardized assessment including cognitive and motor tests by a neurologist via video conferencing and then completed a survey. Primary outcomes assessed were (a) proportion of participants who completed the remote assessments; (b) level of agreement (using Cohen's kappa coefficient) of patient-reported data with that of a neurologist; and (c) interest in future virtual research visits. Results: The self-reported diagnosis of Parkinson's disease was confirmed in all cases ( k = 1.00). The level of agreement for age of symptom onset ( k = 0.97) and family history ( k = 0.85) was very good but worse for falling ( k = 0.59), tremor ( k = 0.56), light-headedness ( k = 0.31), and urine control ( k = 0.15). Thirty-eight (76%) of the 50 participants completed a post-assessment survey, and 87% of respondents said they would be more or much more willing to participate in future clinical trials if they could do research visits remotely. Conclusion: Remote clinical assessments of individuals with known genotypes were conducted nationally and rapidly from a single site, confirmed self-reported diagnosis, and were received favorably. Direct-to-consumer genetic testing and virtual research visits together may enable characterization of genotype and phenotype for geographically diverse populations.